2021
DOI: 10.1111/ejss.13147
|View full text |Cite
|
Sign up to set email alerts
|

Functional root trait‐based classification of cover crops to improve soil physical properties

Abstract: Cover crop use is a well‐established soil conservation technique and has been proven effective for erosion control and soil remediation in many arable systems. Whereas the obvious protection mechanism of cover crops occurs through the canopy, plant roots perform multiple functions. It is important to consider the soil functions delivered by different root systems in order to increase the uptake of cover crops for sustainable soil and water management. A classification of cover crop root systems up to 0.6 m dee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 47 publications
(46 reference statements)
0
19
1
Order By: Relevance
“…Additionally, a greenhouse study by Hudek et al. (2021) found some species of brassica cover crops increased aggregate stability and that all brassicas tested decreased penetration resistance compared with no cover crop in the top 25 cm of soil.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a greenhouse study by Hudek et al. (2021) found some species of brassica cover crops increased aggregate stability and that all brassicas tested decreased penetration resistance compared with no cover crop in the top 25 cm of soil.…”
Section: Introductionmentioning
confidence: 99%
“…However, a study in Idaho found that radish (Raphanus sativus L.) cover crops increased aggregate stability after 2 yr (Lehrsch & Gallian, 2010). Additionally, a greenhouse study by Hudek et al (2021) found some species of brassica cover crops increased aggregate stability and that all brassicas tested decreased penetration resistance compared with no cover crop in the top 25 cm of soil. Many studies have examined the effect of cover crops on soil properties in the Southeast.…”
Section: Introductionmentioning
confidence: 99%
“…The root volume positively correlated with the soil macroporosity (r = 0.40, P < 0.05) and the total porosity (r = 0.41, P < 0.05), and the correlation with the bulk density (r = −0.41, P < 0.05) was negative. Hudek et al (2021) also reported that the total root length and root surface area had a significant effect on soil microporosity. Bodner et al (2014) found that greater root density significantly increased the micropore volume by cover crops, but in the meantime reduced the volume of larger pores.…”
Section: Resultsmentioning
confidence: 92%
“…Furthermore, Haruna et al (2018b) found that CC management increased water infiltration parameters. According to Hudek et al (2021), CC significantly increased aggregate stability and microporosity. However, the impact of CC on soil physical properties is inconsistent (Zaibon et al, 2016;Haruna et al, 2018a;Çerçioğlu et al, 2019), and some studies have shown no effect of cover crops on soil properties.…”
Section: Introductionmentioning
confidence: 97%
“…Other research has shown that cover crops can ameliorate the effect of tillage, but only after 10 yr of the same management and in a nonlegume cover crop (Abdollahi & Munkholm, 2014). Fine roots of cover crops and microbial secondary metabolites are known to facilitate the formation and stability of soil aggregates (Hudek et al., 2021; Jastrow et al., 1998). Our data demonstrates that even in the 1st year, CT decreases aggregate MWD relative to FM when cover crops are not planted.…”
Section: Discussionmentioning
confidence: 99%